2014
DOI: 10.3390/e16021134
|View full text |Cite
|
Sign up to set email alerts
|

Signal Processing for the Measurement of the Deuterium/Hydrogen Ratio in the Local Interstellar Medium

Abstract: Abstract:We report on a comprehensive signal processing procedure for very low signal levels for the measurement of neutral deuterium in the local interstellar medium from a spacecraft in Earth orbit. The deuterium measurements were performed with the IBEX-Lo camera on NASA's Interstellar Boundary Explorer (IBEX) satellite. Our analysis technique for these data consists of creating a mass relation in three-dimensional time of flight space to accurately determine the position of the predicted D events, to preci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The analysis of time-of-flight data from IBEX-Lo revealed three atoms of ISN D that accumulated over three observation seasons during the minimum of solar activity (Rodríguez Moreno et al 2013Moreno et al , 2014. A much larger number of D − ions was found in the data, but it was attributed to the terrestrialwater layer covering the conversion surface.…”
Section: Detection Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The analysis of time-of-flight data from IBEX-Lo revealed three atoms of ISN D that accumulated over three observation seasons during the minimum of solar activity (Rodríguez Moreno et al 2013Moreno et al , 2014. A much larger number of D − ions was found in the data, but it was attributed to the terrestrialwater layer covering the conversion surface.…”
Section: Detection Methodsmentioning
confidence: 99%
“…These latter authors suggested that the detection of just several individual ISN D atoms during one year of IBEX operation during low solar activity can be expected. Based on this insight, Rodríguez Moreno et al (2013) and Rodríguez Moreno et al (2014) found evidence for ISN D in the IBEX-Lo data, albeit based on fewer than 10 atoms, along with many more D atoms sputtered off the terrestrial-water layer covering the IBEX-Lo conversion surface. Clearly, acquiring a number of ISN D atoms on IMAP that would permit a statistical analysis with a reasonable confidence requires identifying the best suitable times and observation geometries during the mission.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Hydrogen Depletion Region ISN Hydrogen Density Radiation Pressure Predicted by models and measured by Cassini [12], Voyager [13], New Horizons (distance dependence, [14,15]), and IBEX-Lo (solar cycle dependence, [16]) New Horizons measures nH (r>20au) higher by ~40% than Ulysses at 5 au [14] IBEX-Lo measurements of ISN H at 1 au indicate a significant role of the solar radiation pressure in data interpretation [17,18] Ne/O and D/H Inside Heliosphere ENA at 1 au vs. 10 au Hydrogen Helioglows Interpretation of heavy element species of ISNs measured at 1 au is sensitive to details of ionization models [8,19,20]. Determination of the Ne/O and D/H ratios from 1 au is difficult and uncertain [20,21].…”
Section: Key Findings Driving Exploration Of the Outer Heliospherementioning
confidence: 99%
“…Rigorous analysis of the individual counts measured with IBEX-Lo from 2009–2011 during low solar activity in energy bins from 10 eV to 100 eV (Rodríguez Moreno et al. 2013 , 2014 ) also allowed to identify likely interstellar D atoms. This in-situ method constrained the D/H ratio in the VLISM to , consistent with the D/H ratio of inferred by Hubble spectroscopy for a line of sight measurement of the Local Interstellar Cloud.…”
Section: Observations Of Energetic Neutral Atoms and Interstellar Neu...mentioning
confidence: 99%